2018
DOI: 10.1515/folmed-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and Stimulation of Neuromuscular Tissue (MASONT) for Stroke Survivors

Abstract: Mobilization and Stimulation of Neuromuscular Tissue (MASONT) is a newly invented somatosensory intervention used for the recovery of function in stroke patients. This paper aims to offer a more spherical view on the new technique. To that end, a basic manual of MASONT's application is provided, along with its rational of use. Moreover, clinical observations on the application of the technique and its effects on neurological patients are presented, as well as, a report on its safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…in past years, it was shown that interventions focusing on somatosensory stimulation -similar to MaSoNT -could cause cortical reorganization in stroke survivors and thus trigger the initiation of this sequence of events that would finally lead to recovery [8]. The safety of the technique has been studied and supported in theory [8], and an exploratory study was conducted in a small number of stroke patients [9]. This case study primarily aims to prove the safety of MaSoNT.…”
Section: Introductionmentioning
confidence: 99%
“…in past years, it was shown that interventions focusing on somatosensory stimulation -similar to MaSoNT -could cause cortical reorganization in stroke survivors and thus trigger the initiation of this sequence of events that would finally lead to recovery [8]. The safety of the technique has been studied and supported in theory [8], and an exploratory study was conducted in a small number of stroke patients [9]. This case study primarily aims to prove the safety of MaSoNT.…”
Section: Introductionmentioning
confidence: 99%